Perbandingan Perbandingan Model Pembelajaran Kooperatif Tipe Jigsaw dan Tipe STAD Terhadap Kemampuan Numerik Siswa Kelas VII di SMPN 14 Pekanbaru: Comparison of Jigsaw Type and STAD Type Cooperative Learning Models on Numerical Ability of Seventh Grade Students at SMPN 14 Pekanbaru - Octaviana, Triwulan; Amelia, Sindi (EDUPEDIA PUBLISHER, 2024)
Purpose: This research aims to compare the Jigsaw type and STAD type cooperative learning models in terms of their impact on the numerical abilities of seventh-grade students at SMPN 14 Pekanbaru. Methodology: The study follows a quasi-experimental design with a non-equivalent control group. The population included all seventh-grade students at SMPN 14 Pekanbaru for the 2023/2024 academic year, totaling 199 students. The research sample consisted of Class VII.1 as experimental group 1, using the STAD type, and Class VII.5 as experimental group 2, using the Jigsaw type. The data collection instrument employed was a test technique, and data analysis involved descriptive statistical analysis and posttest inferential statistical analysis. Findings: The results of the Mann-Whitney U test revealed that the average posttest score for the STAD class was 32.48, whereas for the Jigsaw class, it was 21.31. Consequently, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. Significance: This indicates a significant difference in numerical ability between students taught using the Jigsaw type and those taught using the STAD type cooperative learning model. Specifically, the STAD type was found to be more effective than the Jigsaw type in enhancing students' numerical abilities.